2014
DOI: 10.1377/hlthaff.2013.0702
|View full text |Cite
|
Sign up to set email alerts
|

Capitation Combined With Pay-For-Performance Improves Antibiotic Prescribing Practices In Rural China

Abstract: Pay-for-performance in health care holds promise as a policy lever to improve the quality and efficiency of care. Although the approach has become increasingly popular in developing countries in recent years, most policy designs do not permit the rigorous evaluation of its impact. Thus, evidence of its effect is limited. In collaboration with the government of Ningxia Province, a predominantly rural area in northwest China, we conducted a matched-pair cluster-randomized experiment between 2009 and 2012 to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 19 publications
3
70
0
Order By: Relevance
“…Switching to PFP alone or in combination with capitation reduced spending on drugs, a primary extractive source of revenue, by up to 25% in small-scale experiments (63, 69) but has not had an impact on drug prescriptions in larger contexts (21,86). These reforms, however, did decrease OOP payments (21) and total expenses (86).…”
Section: Impact Of Insurance On Providersmentioning
confidence: 99%
See 1 more Smart Citation
“…Switching to PFP alone or in combination with capitation reduced spending on drugs, a primary extractive source of revenue, by up to 25% in small-scale experiments (63, 69) but has not had an impact on drug prescriptions in larger contexts (21,86). These reforms, however, did decrease OOP payments (21) and total expenses (86).…”
Section: Impact Of Insurance On Providersmentioning
confidence: 99%
“…Additionally, provider payment reforms have reduced the irrational use of drugs and antibiotics (63,86), providing some evidence of improvement in care quality. To date, no evidence has shown that provider payment reforms significantly impact patient satisfaction (21,86). Although length of stay has decreased (21), provider payment reform has not significantly impacted the number of patients (86) (57,69).…”
Section: Impact Of Insurance On Providersmentioning
confidence: 99%
“…Such approaches might include provider payment reform using high-powered incentives (such as capitation and performance pay, which could include specific components for appropriate drug prescription) as well as the provision of health facility quality "report cards" and social accountability interventions. 4,42,43 …”
Section: Exhibitmentioning
confidence: 99%
“…3 Because clinicians both prescribe and sell drugs, they have financial incentives to recommend drug therapies to their patients, even when not clinically appropriate. [4][5][6] Moreover, because patients are generally unable to judge the clinical necessity of drugs recommended to them, providers are able to prescribe-and profit from-unnecessary medications.…”
mentioning
confidence: 99%
“…77 Subsequent trial modifications within the scheme have demonstrated that changing the payment model from fee-for-service to a capitated budget with pay-for-performance was effective in reducing inappropriate and overprescribing of antibiotics. 78 Without altering the overall financing model of healthcare, overprescribing is likely to persist. Financing of state-owned healthcare providers in China relies very heavily on the revenue of pharmaceutical sales (a government-granted 15% mark-up is applied to the procurement price of a pharmaceutical product); 79 as a result, a doctor's salary is typically linked with the volume and financial value of the drugs and services they provide.…”
Section: Case Study 2: Antibiotic Prescription In China: Systemic Andmentioning
confidence: 99%